An investigation into the anaerobic spoilage microbiota of beef carcass and rump steak cuts using high- throughput sequencing. Issue 17 (2nd September 2021) - Esteves, Eden; Whyte, Paul; Mills, John; Brightwell, Gale; Gupta, Tanushree B; Bolton, Declan
ABSTRACT: The presence of anaerobic microflora on fresh beef carcass and rump steaks, which may contribute to meat spoilage, was explored in this study. A total of 120 carcass and 120 rump steak swabs were collected immediately after slaughtering and boning, respectively from five meat plants, anaerobically incubated and enriched at 4°C for 3 weeks. This was followed by DNA extraction and 16S rRNA amplicon sequencing using the Illumina MiSeq, with subsequent bioinformatics analysis. The enriched microbiota of the samples was classified and grouped into 149 operational taxonomic units (OTUs). The microbiota recovered from both sample types consisted mainly of Carnobacterium, with an average relative abundance of 28.4% and 32.8% in beef carcasses and beef rump steaks, respectively. This was followed by Streptococcus, Serratia, Lactococcus, Enterococcus, Escherichia-Shigella, Raoultella and Aeromonas ranging from 1.5 to 20% and 0.1 to 29.8% in enriched carcasses and rump steak swabs, respectively. Trichococcus, Bacteroides, Dysgomonas, Providencia, Paraclostridium and Proteus were also present ranging from 0 to 0.8% on carcass and 0 to 1.8% on rump steak swabs, respectively. Alpha and beta diversity measurements showed limited diversity between the two sample types, but some differences between samples from the beef plants investigated were evident. This study highlights the presence of potential spoilage bacteria, mainly anaerobic genera on and between carcass and rump steaks, as an indication of contamination on and between these samples. Abstract : Microbial spoilage of beef carcass and rump steak cuts.